The Unamendable Articles of the 1945 Constitution - Luthfi Widagdo Eddyono (The Constitutional Court of the Republic of Indonesia, 2016)
The amendments of the 1945 Indonesian Constitution between 1999 and 2002 have significantly changed the state system in Indonesia. In such a short period, the Constitution has been amended four times, provokes enormous additional norms and causes the establishment of several new institutions, including the Constitutional Court and Judicial Commission. However, after the amendments to the 1945 Indonesian Constitution on Chapter XVI about Amendments to the Constitution, the framers of the amended Constitution created Article 37 paragraph (5) that stated, the form of the unitary state of the Republic of Indonesia may not be amended. The Preamble is also implicit unamendable. My purpose in this article is to understand the original intent of Article 37 paragraph (5) of the 1945 Indonesian Constitution, the real function of the article and also to describes original intent arguments explaining why the Preamble of the Constitution also unamendable. Before the amendments between 1999 and 2002, there is no article and provision like that, especially in the original 1945 Constitution. At last, I found that two important points that explain why this new provision created. First, the framers still afraid of separatism based on experience in 1950’s when federalism occurred in Indonesia. Second, the procedure to amend the articles of the 1945 Constitution shows that the framers only wants to strengthen the important system of unitary state because there is no differences process to amend articles of the 1945 Constitution.